ON THE POSSIBILITY OF ELOQUENCE IN SCIENTIFIC PROSE GENRES (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-21-31The article is devoted to the debatable topic of determining the possibilities of using expressive language means in modern scientific prose. The transition from classical to post-non-classical science was accompanied by significant changes in the stylistics of scientific prose. Post-non-classical science, which develops under the conditions of interpenetration of various types of discourse, forms fundamentally new conceptual notions and does not deny expressive means and emotional components in the research process. Moreover, it assumes them as having heuristic potential. Despite the obvious antinomy, the informative and expressive functions of the scientific prose genre successfully “coexist” today. They both promote the act of communication in conditions when the content of scientific knowledge depends on the creative abilities of scientists, and the assessment of innovations depends not only on the opinions of the professional scientists, but also on social community opinion. The aim of this research is to identify the reasons for loyalty to the emotiveness of modern scientific discourse, to reveal the patterns and ways of conveying expressiveness in the genre of scientific prose, taking into account the radically changing modern science status. The main methods of this study are textual and stylistic analysis of Russian and English articles and their titles, selected by the authors in scientific journals indexed in authoritative databases and materials of British National Corpus. It is proved that subjective-evaluative expression in the conditions of competition of scientific strategies, pluralism of interpretations is not only possible, but also meets the scientific needs. It was revealed that the volume of expressive vocabulary depends on the genre of scientific prose. The linguistic means of expressiveness, which are used by scientists not only in the humanities, but also in natural sciences and technology, are metaphor, metonymy, epithets, intensifying adverbs, quantifiers, the use of precedent texts, assertion of the author's style and gender identity.Key words: expressiveness, emotions, genre of scientific prose, scientific style, scientific article, linguistic means, post-non-classical science, ethos of science, scientism, language functions